Проблемы радиобиологии калифорния-252 - Москалев Ю. И. Юрий Иванович; Стрельцова В. Н. Вера Николаевна; Степанов С. В. Сергей Викторович; Жорова Е. С. Елена Соломоновна (Москва, Энергоатомиздат, 1985)
Авт. указаны в вып. дан.